SCHOOL HEAD MANAGEMENT IN REALIZING CHILD-FRIENDLY EARLY CHILDHOOD EDUCATION INSTITUTION - Musyafa Ali; Siti Baro'ah; Ahmad Aji Jauhari Ma’mun (PROCEEDING AL GHAZALI International Conference, 2023)
The rise of cases of violence and bullying against children in educational institutions has become a phenomenon that attracts a lot of public attention. This is because the impact of the case harms many parties, this is also what attracts the attention of educational institution managers to create child-friendly schools. The purpose of this study is to examine and analyze the management of school principals in realizing child-friendly early childhood education institutions. This research was conducted in PAUD Wadas Kelir Purwokerto. This type of research is a field research using a qualitative descriptive approach. Data collection is done by observation, interviews, and documentation. Data analysis is done by collecting data, reducing data, verifying data and drawing conclusions. The results of this study show that managerial efforts made by school principals in order to realize child-friendly early childhood education institutions are carried out by managing six things, namely educator management, classroom management, learning management, learning environment management, child rights management, and parent involvement management